Subaltern masculinity and modern colonial patriarchy Lurgio Gavilán Sánchez’s memoirs - Muñoz-Díaz, Javier (2022)
In this article, I will analyze the gender system and the construction of masculinity in the autobiographical writing of Lurgio Gavilán Sánchez. I offer a textual and hermeneutical analysis of the second stage of his writing, which begins with the «Epilogue» of the 2017 reissue of Memorias de un soldado desconocido and includes Cartas al teniente Shogún from 2019. In this second stage, the Gavilán Sánchez’s place of enunciation is a generation with coordinates of geographical region, social class, and gender —the ex-soldiers from Ayacucho who participated in the Internal Armed Conflict - IAC. For the role of narratario or implicit reading audience, the generation of ex-soldiers coexists with Lieutenant Shogun, who becomes the model of masculinity, paternity, and guiding principle in Gavilán Sánchez’s goal of recovering the family dimension. His writing employs religious language and a melodramatic mode to narrate his peers’ and own interactions with this military and other paternal figures. I propose that the figure of Shogun, an emblem of humanitarian and democratizing practice according to Gavilán Sánchez, actually embodies the modern colonial patriarchy and subordinates the memorialist’s racialized masculinity. Likewise, the melodramatic mode imposes the gender binary of modern colonial patriarchy that depoliticizes women (the case of the Shining Path militant Rosaura).